Graphene Quantum Dots for Fluorescent Labeling of Gelatin‐Based Shear‐Thinning Hydrogels. Issue 7 (20th May 2021) - Nasrollahi, Fatemeh; Nazir, Farzana; Tavafoghi, Maryam; Hosseini, Vahid; Ali Darabi, Mohammad; Paramelle, David; Khademhosseini, Ali; Ahadian, Samad
Abstract : The efficiency of injectable biomaterials as minimally invasive therapeutics significantly relies on biomaterial's characteristics, such as stability, biodegradation rate, and interaction with the host tissue, which requires real‐time tracking of the biomaterials. Fluorescence imaging is considered as a noninvasive technique for monitoring biomaterials; however, the commonly used fluorescent agents are often accompanied by photobleaching and toxicity. Herein, graphene quantum dots (GQDs) are introduced as a biocompatible and stable fluorophore for imaging and noninvasive monitoring of a physically cross‐linked injectable shear‐thinning biomaterial (STB) of gelatin–silicate nanoplatelets. Silicate nanoplatelets and GQDs serve as the physical cross‐linkers of gelatin making electrostatic interaction with gelatin chains. Different STB‐GQDs formulations are assessed in terms of fluorescence intensity, injectability, thermal stability, and cellular biocompatibility. STB‐GQDs with 0.06% GQDs, 6% solid material, and 50% silicate in the solid material show the strongest in vitro fluorescence and the highest thermal stability. In vivo monitoring of STB‐GQDs is also achieved through fluorescent imaging where incorporated GQDs exhibit a robust and stable signal, suggesting their promising applications in long‐term tracking of gelatin‐based STBs. Abstract : Graphene quantum dots (GQDs) are introduced as a biocompatible and stable fluorophore for imaging and noninvasive monitoring of an injectable shear‐thinning biomaterial (STB) of gelatin–silicate nanoplatelets. The biomaterial shows strong in vitro fluorescence and thermal stability. A robust and stable fluorescence signal of STB‐GQDs in vivo is also achieved for long‐term tracking of gelatin‐based STBs.